Characteristics of Pulmonary TB Patients in The Region Health Center - Gurusinga, Rahmad (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2024)
Pulmonary tuberculosis (TB), caused by Mycobacterium tuberculosis, is an infectious disease that spreads globally and is the second largest cause of death after HIV/AIDS. According to the World Health Organization (WHO), approximately one third of the world's population is believed to be infected with M. tuberculosis, with 10% of them at risk of developing the disease. Tuberculosis germs generally infect the lungs, but can also attack other body organs. Transmission occurs through close contact with pulmonary tuberculosis sufferers who have BTA (+), where each sufferer can transmit this disease to 10-15 people each year. Factors that influence a person's risk of developing pulmonary tuberculosis include weakness in the body's immune system, which can be caused by a lack of nutritional intake and other factors. The aim of this research is to find out the characteristics of pulmonary TB sufferers. The research method used was descriptive analytical, with 37 pulmonary TB sufferers as samples selected using accidental sampling techniques at Community Health Center X. The measuring instrument used was a questionnaire, and the measurement results were analyzed using a frequency distribution table. The results of the study showed that the majority of tuberculosis (TB) sufferers were over 45 years old, reaching 54.1%, the majority of TB sufferers were men, with a percentage of 70.3%, the majority of TB sufferers had elementary school education, with the number reaching 48 .6%, The majority of TB sufferers work as farmers and employees, which reaches 32.4%, The majority of TB cases are old cases, accounting for 56.8%, The majority of TB sufferers receive treatment regularly, reaching 54.1%, and The majority of TB sufferers TB was declared cured after treatment, with the number reaching 75.7% of the total sample. The conclusion is that these results reflect the general profile of TB sufferers in the population studied. This provides an overview of the demographic characteristics, disease history, and response to treatment of TB sufferers in the context of the research conducted. It is recommended that this data can be used as a basis for planning more effective interventions and treatment strategies as well as more targeted prevention efforts in controlling TB disease in the future.